Therapeutic Strategies to Spinal Cord Injury - Pavla Jendelova (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
ca. 200 words; this text will present the book in all promotional forms (e.g. flyers). Please describe the book in straightforward and consumer-friendly terms. This Special Issue gathers eight research articles covering a broad range of strategies on how to combat spinal cord injuries, from searching for therapeutic target molecules, tackling inflammatory reactions, utilizing cell therapy or cell-based products, combined strategies for axonal plasticity assessment, and prevention of post-surgical epidural adhesions. Moreover, four reviews cover recent findings about the role of stress-activated protein kinases in SCI; progress in stem cell therapies; the mechanisms and benefits of activity-based physical rehabilitation therapies with adjuvant testosterone; and, finally, translational regenerative therapies for chronic spinal cord injury.